Respostas

A melhor resposta!
2014-03-24T21:46:18-03:00
Como visto em http://brainly.com.br/tarefa/404890 temos que

b_{ii}=-a_{ii}, \ i\in \mathbb{N}, \ 1\leq i\leq n

Daí, escrevendo todos os termos do somatório, teremos:

\sum\limits^n_{i=1}b_{ii}=b_{11}+b_{22}+b_{33}+\ldots+b_{nn} \\ \\ \sum\limits^n_{i=1}b_{ii}=-a_{11}-a_{22}-a_{33}-\ldots-a_{nn} \\ \\ \mathrm{Colocando \ o \ - \ em \ evid\^{e}ncia} \\ \\ \sum\limits^n_{i=1}b_{ii}=-(a_{11}+a_{22}+a_{33}+\ldots+a_{nn}) \\ \\ \boxed{\boxed{\sum\limits^n_{i=1}b_{ii}=-\sum\limits^n_{i=1}a_{ii}}}
2 5 2